Induction of homologous and cross-reactive GII.4-specific blocking antibodies in children after GII.4 New Orleans norovirus infection - Blazevic, Vesna; Malm, Maria; Vesikari, Timo (Journal of medical virology, 2015)
Noroviruses (NoVs) are major causative agents of acute gastroenteritis (AGE) in children worldwide and the most common viral cause of AGE in countries where rotavirus incidence has been eliminated by vaccination. Previous infections with the dominant GII.4 NoV genotype confer only partial protection against evolving immune escape variants that emerge every few years. The objective of this work was to investigate GII.4‐specific homologous and cross‐reactive antibody responses in young children after NoV GII.4‐2009 New Orleans (NO) infection. Virus‐like particles (VLPs) representing GII.4‐1999, GII.4‐2009 NO, and GII.4‐2012 Sydney genotypes were used in ELISA and histo‐blood group antigen blocking assays to examine acute and convalescent sera of five children <2 years of age infected with GII.4‐2009 NO. GII.4‐2009 NO infection induced IgG seroconversion to all three tested NoV GII.4 variants. Homologous blocking antibodies to GII.4‐2009 NO were detected in each convalescent sera. Fourfold increase in cross‐blocking antibodies to GII.4‐2012 Sydney was observed in 4/5 subjects, but no child developed cross‐blocking antibodies to GII.4‐1999. In conclusion, antibodies induced in young children after norovirus GII.4 infection are targeted against the causative variant and may cross‐protect against strains that are closely related, but not with more distinct and earlier GII.4 genotypes. J. Med. Virol. 87:1656–1661, 2015. © 2015 Wiley Periodicals, Inc.